An Investigation of Australian Muslims’ Help-Seeking Pathways for Mental Health Problems - Lucy Jane Verwey (Journal of Muslim Mental Health)
This research involves an exploration of Australian Muslims’ attitudes, perceptions, and experiences of mental health and accessing professional treatment services. It utilized a mixed-methods design consisting of in-depth interviews and a survey. The face-to-face interviews were conducted with practising Muslims in Australia (N = 20) and the online survey was based on the main themes that emerged from the interviews and was completed by the Australian Muslim participants (N = 200). Grounded theory was employed as the underlying approach for the qualitative data collection and analysis. The results revealed that the participants adopted distinct help-seeking pathways, which involved a range of religious and cultural influences. The participants highlighted a need for religiously and culturally appropriate treatment for Muslim clients. Overall, the findings draw attention to the need for theorists, researchers, and clinicians to understand the distinct pathways of seeking mental health when working with Muslim clients.